This action might not be possible to undo. Are you sure you want to continue?

BooksAudiobooksComicsSheet Music### Categories

### Categories

### Categories

Editors' Picks Books

Hand-picked favorites from

our editors

our editors

Editors' Picks Audiobooks

Hand-picked favorites from

our editors

our editors

Editors' Picks Comics

Hand-picked favorites from

our editors

our editors

Editors' Picks Sheet Music

Hand-picked favorites from

our editors

our editors

Top Books

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Audiobooks

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Comics

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Sheet Music

What's trending, bestsellers,

award-winners & more

award-winners & more

Welcome to Scribd! Start your free trial and access books, documents and more.Find out more

The Resource Center

**What makes Algebra different from Arithmetic?
**

The Presence of the Unknown Variable

The Resource Center

Linear Equations in Single Variable

The Resource Center

Solve: (5x – 6) / 3 = 4

x = 18 / 5

The Resource Center

Simplify (3xy – 9y) / (x – 3)

3y But what if x = 3 ?

The Resource Center

Simultaneous Equations

The Resource Center

Solve 3a + b = 15 3b + a = 13

a = 4, b = 3

The Resource Center

3x - y = 6 6x - 2y – 12 = 0

Infinite solutions..

The Resource Center

Quadratic Equations

The Resource Center

Solve (x - 5x + 6) = 0

2

(x2 - 3x - 2x + 6) = 0 x (x - 3) - 2 (x - 3) = 0 (x - 2) (x - 3) = 0 x = 3 or x = 2

The Resource Center

Solve : 2x – 17x + 21 = 0

2

X = 3/2 and x = 7

The Resource Center

General Solution of 2 ax + bx + c = 0 (a ≠ 0)

x = [ -b + √ (b2 - 4ac) ] / 2a x = [ -b - √ (b - 4ac) ] / 2a

2

The Resource Center

**In ax + bx + c = 0 , what is the Sum of the roots?
**

2

- b/a

The Resource Center

**In ax + bx + c = 0 , what is the product of the roots?
**

2

c/a

The Resource Center

**In ax + bx + c = 0, when are the two roots equal?
**

2

When b = 4ac

2

The Resource Center

**In ax + bx + c = 0, when are the roots reciprocal of each other?
**

2

When c = a

The Resource Center

Inequalities

The Resource Center

If x ≥ 3, is x + 2 ≥ 3 + 2 ?

Yes

The Resource Center

If x ≥ 3, is x - 4 ≥ 3 - 4 ?

The same number can be added or subtracted without changing the truth of the inequality

The Resource Center

If x ≥ 3, is x * 2 ≥ 3 * 2 ?

Both the sides can be multiplied or divided by the same number without changing the truth of the inequality.

The Resource Center

If x ≥ 3, is x * (- 2) ≥ 3 * (-2) ?

No. A negative number multiplied on both sides, reverses the sign of the inequality.

The Resource Center

Solve the inequality (5x – 1) / -2 < 3

x >-1

The Resource Center

Solve x – 7x - 8 < 0

2

**x > 8 and x < -1 (Not possible) x < 8 and x > -1 (Possible) OR -1 < x < 8
**

The Resource Center

Sequences and Series

The Resource Center

**What is the next term in the sequence? 9, 6, 3, 0, -3,....
**

This is an AP, with common difference (-3).

The Resource Center

**What is the next term in the sequence? 4, -2, 1, -1/2,...
**

This is a GP, with common ratio (- 1/2)

The Resource Center

**Sum of the first n integers
**

= n (n + 1) / 2

The Resource Center

**Find the sum of the series a, a+d, a+2d,... a+(n–1) d
**

(a is expressed n times) = na + d [ 1 + 2 + 3 + ..... (n-1) ] = na + (n-1)( n – 1 +1) d / 2 = n/2 [ 2a + (n – 1) d ]

The Resource Center

In other words, the sum of an AP of n terms with first term “a” and common difference “d” is ...

= n/2 [ 2a + (n – 1) d ]

The Resource Center

**Sum of a GP of n terms with first term “a” and common ratio “r”
**

= a ( r - 1) / ( r - 1)

n

The Resource Center

**What is the seventh term of the sequence 1, 1/4, 1/9, 1/16, …? Is it a progression?
**

Seventh term is 1/49. It is not a progression.

The Resource Center

**Find the sum of the series 1, 2, 3, 4, ... 15?
**

15 (15 + 1) / 2 = 120

The Resource Center

The first term of an AP is 5 and the common difference is 4. What is the sum of the first six terms?

90

The Resource Center

**Find the fourth term of a th GP if the 6 term is 20 and the common ratio is 2.
**

5

The Resource Center

**A quick revision of concepts covered till now ...
**

The Resource Center

If ab = bc, then is a = c?

Only if b <> 0

The Resource Center

General Solution of 2 ax + bx + c = 0 (a ≠ 0)

x = [ -b + √ (b2 - 4ac) ] / 2a x = [ -b - √ (b - 4ac) ] / 2a

2

The Resource Center

If a > b, is ac > bc?

Only if c is positive.

What if c is negative?

Then > becomes <

The Resource Center

a + b + c - 3abc =

3 3 3

**(a + b + c) x 2 2 2 (a + b + c - ab - bc - ca) What if (a + b + c) = 0? 3 3 3 a + b + c will be = 3abc
**

The Resource Center

a -b =

n n

where n is an element of N. n-1 n-2 n-1 (a-b) (a + a b +…… + b )

The Resource Center

Find the value of 2 1 2 x + ( /x ) 1 if x + ( /x) = 3

The Resource Center

Given that x + (1/x) = 3 Squaring both the sides we get [x + (1/x)]2 = 9 x2 + 1/x2 + 2 = 9 2 1 2 x + /x = 7

The Resource Center

**If x = a (b-c), y = b (c-a), z = c (a-b), find the value of x 3 y 3 z 3 ( /a) + ( /b) + ( /c)
**

The Resource Center

**We can write x /a = (b - c), y /b = (c - a), z /c = (a - b) And x /a + y/b + z/c = 0 x 3 y 3 z 3 so, ( /a) + ( /b) + ( /c) = 3xyz / abc
**

The Resource Center

**Find the value of 2 2 2 a + b + c - 2ab - 2ac + 2bc if a = 17, b = 15, and c = 13
**

The Resource Center

**We can write the given equation as 2 (a - b - c) Putting the values of a, b, and c, 2 the value is (17 - 15 - 13) = 121
**

The Resource Center

Simplify {(a - b ) + (b - c ) + (c -a ) } -----------------------------------------3 3 3 {(a-b) + (b-c) + (c-a) }

2 2 3 2 2 3 2 2 3

The Resource Center

**Let x = a - b , 2 2 y = b - c and 2 2 z=c -a So, x + y + z = 0 3 3 3 Therefore x + y + z = 3xyz
**

2 2

The Resource Center

**So, the numerator 2 2 2 2 2 2 = 3 (a -b ) (b - c ) (c -a ) and the denominator = 3(a-b) (b-c) (c-a) Hence, the ratio = (a+b)(b+c)(c+a)
**

The Resource Center

Find the value of 2 (a+1) * (1-a) * (1+a+a ) * 2 6 (1-a+a ) * (1+a )

The Resource Center

**We can write the above equation as: 2 (a+1) * (1-a+a ) * 2 6 (1-a) * (1+a+a ) * (1+a ) 3 3 6 = (1+a ) * (1-a ) * (1+a ) 6 6 = (1-a ) * (1+a ) 12 = (1-a )
**

The Resource Center

**Find the value of b-a c-a 1/(1+x +x ) + a-b c-b 1/(1+x +x ) + a-c b-c 1/(1+x +x )
**

The Resource Center

Upon solving we get a b c a b c (x +x +x )/(x +x +x ) = 1

The Resource Center

**If a + b + c = 0, find the value of 2 2 2 1/(b + c - a ) + 2 2 2 1/(c + a - b ) + 2 2 2 1/(a + b - c )
**

The Resource Center

Given that (a + b + c)= 0, 2 2 (a + b) = (-c) 2 2 2 or, a + b - c = -2ab 2 2 2 similarly b + c - a = -2bc & 2 2 2 c + a - b = -2ca Thus, the equation becomes (1/-2bc) + (1/-2ca) + (1/-2ab) = (a + b + c) / -2abc = 0

The Resource Center

**Find the value of {17 + 4 (17) + 16} --------------------------------2 (17 + 38)
**

4 2

The Resource Center

**It can be written as 4 2 2 4 {(17) + (2) (17) + (2) } ----------------------------------2 2 {17 + (17)(2) + (2) 2 2 = (17) - (17)(2) + (2) = 259 4 4 2 2 Since a + b + a b = 2 2 2 2 (a + b + ab)(a + b - ab)
**

The Resource Center

**For what value of m will
**

(m+1)x + 2(m+3)x + m + 8 = 0 have

2

equal roots

The Resource Center

b - 4ac =0

2

Hence, 2 4 (m + 3) - 4 (m + 1)(m + 8) = 0 Upon solving we get m = 1/3

The Resource Center

**A quick review of the formulae
**

The Resource Center

(a + b) =

2

a + b + 2ab

2 2

The Resource Center

(a - b)

2 2

2

= a + b - 2ab

The Resource Center

(a + b) - (a - b) =

2 2

4ab

The Resource Center

a -b =

2 2

(a + b) (a - b)

The Resource Center

(a + b + c) =

2

a2 + b2 + c2 + 2(ab + bc + ca)

The Resource Center

(a - b + c) =

2

a + b + c + 2(ac - bc - ab)

2 2 2

The Resource Center

(a + b - c) =

2

a + b + c + 2(ab - ac - bc)

2 2 2

The Resource Center

(a + b) =

3

a + b + 3ab(a + b)

3 3

The Resource Center

a +b +ab =

4 4 2 2

(a + b + ab)(a + b - ab)

2 2 2 2

The Resource Center

a +b=

4 4

(a - √2ab + b ) (a + √2ab + b )

2 2 2 2

The Resource Center

a + b + c - 3abc =

3 3 3

(a+b+c)(a + b + c - ab - bc-ca)

2 2 2

What if (a + b + c) = 0? 3 3 3 a + b + c = 3abc

The Resource Center

a -b = n is an element of N

n n

(a - b) (a

n-1

+ a b +…… + b )

n-2 n-1

The Resource Center

algebra

algebra

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue listening from where you left off, or restart the preview.

scribd